Pengaruh Disiplin Dan Lingkungan Kerja Fisik Terhadap Kinerja Karyawan Pada PT. Candi Malindo Bangkit Tangerang Selatan - Putri Oktapiani; Indri Indirasari (CV. KAMPUS AKADEMIK PUBLISING, 2024)
The aim of this research is to determine the influence of the work discipline and work environment on employee performance at PT Candi Malindo Bangkit Tangerang Selatan. The method used in this research is a quantitative method. The population in this study was all 60 employees. The sampling technique in this research uses a saturated sampling technique or where all members of the population are sampled. The data analysis technique used is statistical analysis with validity test, reliability test, classical assumption test, multiple linear regression test, correlation coefficient analysis, coefficient of determination analysis, as well as T hypothesis test and F hypothesis test. The results of the research show that partial hypothesis testing: The work discipline (X1) has a positive and significant effect on employee performance (Y) with a calculated t value greater than t table or (8,042 > 2,002), partially the work environment variable (X2) has a positive and significant effect on employee performance (Y) with The calculated t value is greater than the t table or (11,539 > 2,002) and simultaneously the work discipline (X1) and work environment (X2) have a positive and significant effect on employee performance (Y) with the calculated F value being greater than the F table or (56,645>3,16). This is also reinforced by the probability of 0.000 < 0.05. Thus H0 is rejected and Ha3 is accepted. This means that there is a simultaneous positive and significant influence between the physical work discipline work environment on employee performance at PT Candi Malindo Bangkit Tangerang Selatan.